Combined use of rheology and portable low-field NMR in cystic fibrosis patients. (November 2021) - Abrami, Michela; Maschio, Massimo; Conese, Massimo; Confalonieri, Marco; Gerin, Fabio; Dapas, Barbara; Farra, Rossella; Adrover, Alessandra; Torelli, Lucio; Ruaro, Barbara; Grassi, Gabriele; Grassi, Mario
Abstract: Background: As most cystic fibrosis ( CF ) patients progress to respiratory failure, lung functionality assessment is pivotal. We previously developed a test that indirectly monitors airways (inflammation/functional test) by measuring the spin-spin relaxation time ( T 2m ) of the water hydrogens present in CF sputum. Here the T 2m significance in the monitoring of CF lung disease was further investigated by studying the correlation of T 2m with: 1) sputum viscoelasticity, 2) mucociliary clearability index ( MCI )/cough clearability index ( CCI ) and 3) sputum average mesh-size. Methods: Sputum samples from 25 consenting CF subjects were analyzed by rheology tests (elastic modulus G and zero shear viscosity η0 ) and Low Field Nuclear Magnetic ( LF-NMR ) resonance ( T 2m ). MCI / CCI were calculated from the rheological parameters. The average mesh-size (ξ) of the sputum structure was then evaluated by rheology/ LF-NMR, together with FEV 1 for each patient. Results: There was an inverse correlation between G and η0 versus T 2m, indicating that a worsening of the lung condition ( T 2m - FEV 1 drop) is paralleled by an increase in sputum viscoelasticity ( G and η0 ) favoring mucus stasis/inflammation. A direct correlation was also observed between T 2m and MCI / CCI, showing that T 2m provides information as to airway mucus clearing. Moreover, there was a direct correlation between T 2m and the average sputum mesh size (ξ). Conclusions: We demonstrated a correlation between T 2m (measured in CF patient's sputum) and the sputum viscoelasticity/average mesh-size and with MCI / CCI, parameters related to airway mucus clearing. Thus, the present data strengthen the potential of our test to provide indirect monitoring of airway disease course in CF patients as T 2m depends on mucus solid concentration and nanostructure.